Advances and Trends in Development of Plant Factories - Ralph Panstruga (Frontiers Research Topics, 2017)
The plant factory is a facility that aids the steady production of high-quality vegetables all year round by artificially controlling the cultivation environment (e.g., light, temperature, humidity, carbon dioxide concentration, and culture solution), allowing growers to plan production. By controlling theinternal environment,plant factories can produce vegetables about two to four times faster than by typical outdoor cultivation. In addition, as multiple cultivation shelves (a multi-shelf system) are used, the mass production of vegetables in a small space is facilitated. This research topic presents some new trends on intelligent measuring systems; environment controlled and optimization; favonoids; phenylpropanoids, transcriptomes, and bacteria.